2013
DOI: 10.2174/1745017901309010157
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and Parenting in Adult Patients with Anxiety Disorders

Abstract: Background:The literature suggests that dysfunctional parenting and insecure attachment may increase risk of anxiety-related psychopathology. This study aimed at testing the association between anxiety disorders, attachment insecurity and dysfunctional parenting while controlling for factors usually not controlled for in previous studies, such as gender, age, and being ill.Methods:A sample of 32 non-psychotic inpatients with SCID-I diagnosis of an anxiety disorder, either alone or in comorbidity, was compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
(45 reference statements)
3
16
0
1
Order By: Relevance
“…In their study, Brumariu & Kerns (2010) reported a relationship between the mother-child attachment style and different anxiety disorders. This relationship was also demonstrated in other studies (Picardi et al, 2013;Esbjorn et al, 2012). A study conducted by Catherine et al (2012) showed that the insecure attachment style is associated with greater anxiety responses.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…In their study, Brumariu & Kerns (2010) reported a relationship between the mother-child attachment style and different anxiety disorders. This relationship was also demonstrated in other studies (Picardi et al, 2013;Esbjorn et al, 2012). A study conducted by Catherine et al (2012) showed that the insecure attachment style is associated with greater anxiety responses.…”
Section: Introductionsupporting
confidence: 71%
“…From childhood until old age, individuals try to survive for the final goal of establishing intimacy. But every individual has a different attachment style that is indicative of his personal differences affected by the perception he has of his own and others' beliefs (Bowlby, 1969 ;Picardi et al, 2013). The theory of attachment and personal relationships affected by early experiences in development and its relationship with later personality development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents who nurture their infants and who willingly fulfil their infants’ physiological and psychological needs for security and emotional closeness will foster a better and more stable emotional development in their offspring, who will be able to cope with stressful events in an adaptive way. By contrast, children who experience poor parenting tend to develop poorer emotional pathways and will react to distress with maladaptive responses (Francis & Meaney, 1999; Picardi et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…En los últimos años, numerosos estudios han intentado establecer una relación entre el tipo de apego y el desarrollo posterior de psicopatología (Aaronson et alt. 2006;A Picardi et alt 2013). Las aportaciones también de P Fonagy (2006P Fonagy ( -2016 han contribuido, en este sentido, a establecer un puente entre las teorías del apego y la psicopatología.…”
Section: Iarpp-españa Barcelonaunclassified